Respon Pertumbuhan Bibit Kakao Klon Sulawesi 1 Terhadap Berbagai Media Tanam (Theobroma Cacao L.) - Fransiska Bete; Nikmah Nikmah; Linda Bachrun (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2024)
This study was conducted with the aim to determine the effect of media and clones on the growth of cocoa seedlings. This research was conducted at the Experimental Garden of the Faculty of Agriculture, Borobudur University in September-November 2022. This research used Factorial Randomized Group Design (RAK), the first factor was 4 kinds of planting media (soil: compost: husk, soil: compost: sand, soil: compost: husk: cocopeat, soil: compost: sand: cocopeat) and the second factor was two cocoa clones (Sulawesi 1 and Sulawesi 2). The data obtained will be further tested using the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that there was an interaction effect of planting media and cocoa clones on the number of leaves and stem diameter at the age of 12 weeks after planting with the best treatment M1S2. In planting media there is a significant effect on plant height 6, 10 weeks after planting with the best treatment M4, number of leaves 4 weeks after planting with the best treatment M4, stem diameter 4 weeks after planting with the best treatment M4. In cocoa clones there is no significant effect at various ages, but tend to be highest in Sulawesi 1 clone in plant height, number of leaves and stem wet weight while in Sulawesi 2 clone tend to be highest in parameters of stem diameter, root length and root wet weight